Dark resonance spectra of trapped ions under the influence of micromotion - Nuñez Barreto, Nicolás A.; Bonetto, Muriel; Luda, Marcelo A.; Cormick, Cecilia; Schmiegelow, Christian T. (Frontiers in Quantum Science and Technology, 2024)
We study the influence of micromotion on the spectrum of trapped ions with a lambda-type level scheme, leading to dark resonances due to coherent population trapping. We work with calcium ions trapped in a ring-shaped Paul trap, in which one can compensate excess micromotion for only one ion of the crystal. We observe that micromotion affects the shapes of the dark resonances and causes the appearance of "echoes" separated by intervals given by the drive frequency. We present a theoretical model that provides good fits to the measurements and can be used to estimate the amplitude of the micromotion modulation of the atomic motion. We estimate an effective temperature of the ions from the spectra and observe clear micromotion heating as well as impaired cooling for sufficiently large excess micromotion.